2019
DOI: 10.1613/jair.1.11876
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Abstention based on Preference Extensions: Positive Results and Computer-Generated Impossibilities

Abstract: Voting rules allow multiple agents to aggregate their preferences in order to reach joint decisions. A common flaw of some voting rules, known as the no-show paradox, is that agents may obtain a more preferred outcome by abstaining from an election. We study strategic abstention for set-valued voting rules based on Kelly's and Fishburn's preference extensions. Our contribution is twofold. First, we show that, whenever there are at least five alternatives and seven agents, every Pareto-optimal majoritarian voti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…When assuming that voters have incomplete preferences over sets or lotteries, participation and Condorcetconsistency can be satisfies simultaneously and positive results for common Condorcet-consistent voting rules have been obtained by Brandt [7] and Brandl et al [4,5,6]. Abstention in slightly different contexts than the one studied in this paper recently caught the attention of computer scientists working on voting equilibria and campaigning [16,1].…”
Section: Related Workmentioning
confidence: 83%
See 1 more Smart Citation
“…When assuming that voters have incomplete preferences over sets or lotteries, participation and Condorcetconsistency can be satisfies simultaneously and positive results for common Condorcet-consistent voting rules have been obtained by Brandt [7] and Brandl et al [4,5,6]. Abstention in slightly different contexts than the one studied in this paper recently caught the attention of computer scientists working on voting equilibria and campaigning [16,1].…”
Section: Related Workmentioning
confidence: 83%
“…To achieve this, we encode these problems as formulas in propositional logic and then use SAT solvers to decide their satisfiability and extract minimal unsatisfiable sets (MUSes) in the case of unsatisfiability. This approach is based on previous work by Tang and Lin [35], Geist and Endriss [20], Brandt and Geist [8], and Brandl et al [4]. However, it turned out that a straightforward application of this methodology is insufficient to deal with the magnitude of the problems we considered.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rigorous axiomatic foundation and its emphasis on impossibility results, social choice theory is particularly well-suited for computer-aided theorem proving techniques. Apart from work that is directed towards formalizing and verifying existing results (see, e.g., [83,101]), a number of recent papers have proved new theorems with the help of computers [30,32,37,41,43]. This branch of research was initiated by Tang and Lin [128], who reduced well-known impossibility results such as Arrow's theorem to finite instances, which could then be checked by SAT solvers.…”
Section: Computer-aided Theorem Provingmentioning
confidence: 99%
“…Fortunately, when relying on SAT solving, this criticism can be addressed by extracting a human-readable proof from an inclusion-minimal unsatisfiable set of clauses returned by the SAT solver. This approach, pioneered by Brandt and Geist [37], has been successfully applied in several recent papers [30,32,41,43].…”
Section: Computer-aided Theorem Provingmentioning
confidence: 99%
“…2 In the context of strategic abstention (i.e., manipulation by deliberately abstaining from an election), even more positive results can be obtained. Brandl et al [9] have shown that all of the above mentioned SCFs that are strategyproof for strict preferences are immune to strategic abstention even when preferences are weak.…”
Section: Introductionmentioning
confidence: 99%